anonymous
  • anonymous
square root of 2z+9-square root of z+6=o
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
\[\sqrt{2z+9 }-\sqrt{z+6}=0\]
anonymous
  • anonymous
\[\sqrt{2z+9}=\sqrt{z+6}\]
anonymous
  • anonymous
\[\implies \sqrt{2z+9}=\sqrt{z+6} \implies 2z+9=z+6 \implies z=-3\] Plug in the equation and check!!

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
hows the work?
anonymous
  • anonymous
Just substitute in the original equation with z=-3 to check it's the right solution!!
anonymous
  • anonymous
It's right by the way!! So your answer is z=-3
anonymous
  • anonymous
yea i checked!
anonymous
  • anonymous
\[\sqrt{x+8}=x-4\]
anonymous
  • anonymous
What do you think?
anonymous
  • anonymous
x-8=x-16
anonymous
  • anonymous
-8 -8
anonymous
  • anonymous
=8
anonymous
  • anonymous
Well. The first thing you should here is to get rid of the square root. To do so, you should square both sides. Can you do that?
anonymous
  • anonymous
yess
anonymous
  • anonymous
you should do*
anonymous
  • anonymous
Ok. Do it and show me what you get.
anonymous
  • anonymous
\[\sqrt({x-8})^{2}=(x-4)^{2}\]
anonymous
  • anonymous
\[x+8=x+16\]
anonymous
  • anonymous
are you sure about the right hand side?
anonymous
  • anonymous
(x-4)^2 is what?
anonymous
  • anonymous
yes because 4x4=16
anonymous
  • anonymous
all (x-4) is raised to the power of 2. Not only the 4.. So it's like (x-4) times (x-4)
anonymous
  • anonymous
??
anonymous
  • anonymous
:)
anonymous
  • anonymous
Ok.. follow my steps carefully!
anonymous
  • anonymous
First start by squaring both sides: \[(\sqrt{x+8})^2=(x-4)^2\] you did the left hand side, it's the same as x+8.. the right hand side is: \[(x-4)^2=x^2-8x+16\]
anonymous
  • anonymous
Now, the equation will look like: \[x+8=x^2-8x+16 \implies x^2-9x+8=0\] Do you know how to solve a quadratic equation?
anonymous
  • anonymous
Just factorize the expression x^2-9x+8 to get: \[x^2-9x+8=0 \implies (x-8)(x-1)=0 \implies x=1, x=8\] We have two values for x. Check for each one!
anonymous
  • anonymous
You will find that only x=8 is a solution of the equation.

Looking for something else?

Not the answer you are looking for? Search for more explanations.